2004
DOI: 10.1093/aob/mch174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sand Burial on Survival, Growth, Gas Exchange and Biomass Allocation of Ulmus pumila Seedlings in the Hunshandak Sandland, China

Abstract: Ulmus pumila was shown to be tolerant to partial sand burial, but must be protected from complete burial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 23 publications
5
75
1
1
Order By: Relevance
“…Previous studies have demonstrated that wind erosion has negative effects on plant survivorship, growth and reproduction in many dune plants (Marbà and Duarte 1994;Petru and Menges 2004;Yu et al 2008;Li et al 2010a). Sand burial can stimulate plant physiological activity and growth (Shi et al 2004;Perumal and Maun 2006), shifts in biomass allocation patterns (Burylo et al 2011), and the production of adventitious roots (Dech and Maun 2006;Liu et al 2008). Erosion causes plants to fall to the ground where they often become entirely or partly buried (e.g., when they are located at leeward slope and crest of the sand dune), stimulating further deposition of sand and burial on the fallen shoots.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that wind erosion has negative effects on plant survivorship, growth and reproduction in many dune plants (Marbà and Duarte 1994;Petru and Menges 2004;Yu et al 2008;Li et al 2010a). Sand burial can stimulate plant physiological activity and growth (Shi et al 2004;Perumal and Maun 2006), shifts in biomass allocation patterns (Burylo et al 2011), and the production of adventitious roots (Dech and Maun 2006;Liu et al 2008). Erosion causes plants to fall to the ground where they often become entirely or partly buried (e.g., when they are located at leeward slope and crest of the sand dune), stimulating further deposition of sand and burial on the fallen shoots.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we found RMR and root/shoot ratio increased with increased depth. When a plant is buried, soil moisture in the root zone increases and soil temperature decreases (Shi et al 2004). Moreover, high root biomass allocation benefits water absorption (Perumal et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…5), indicating that partial burial might stimulate seedling growth. Many plant species enhanced seedling growth by partial burial compared to complete burial (Shi et al 2004, Zheng et al 2012 For personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the effects of sand burial have been widely reported in the fields of seedling survival (Belcher, 1977;Cheplick and Grandstaff, 1997;Harris and Davy, 1987;Li et al, 2015;Liu et al, 2008;Perumal and Maun, 2006), physiological characteristics (Shi et al, 2004;Wang et al, 2012;Zhao et al, 2015), and reproductive strategies (Liu et al, 2014;Sun et al, 2014;Zhao et al, 2007) on coastal marshes and wetlands plants. In general, it appears to be a thresh- old sand burial depth for each plant species to maintain its vigor and subsequent sustained growth (Maun, 1997).…”
Section: Introductionmentioning
confidence: 99%